Potential use of macroalgae and its symbiont bacteria isolated from tanjung tiram as a source of amylase enzyme - Kusumawati, Herdiani Nur (Jurnal Teknologi Laboratorium, 2020)
This study aimed to extract the amylase enzyme produced by macroalgae and its symbiont bacteria isolated from The Coastal Waters of Tanjung Tiram, Kendari, Southeast Sulawesi and to define its characteristics. Macroalgae is a cultivation commodity in Indonesia that has the potential as a source of enzymes, including amylase enzyme. Amylase is an enzyme that functions to catalyze the hydrolysis reaction of starch and glycogen into maltose, maltotriose, isomaltose, and glucose. Methods used in this study were enzyme extraction, enzyme purification by ammonium sulfate precipitation and dialysis, qualitative assay by iodine test, quantitative assay by DNS method and UV-Vis spectrophotometry. Qualitative assay for amylase activity of macroalgae showing positive results whereas its symbiont bacteria showing no amylase activity. The optimum temperature was 50oC, pH 9 and salt 3 M. Quantitative assay of amylase activity at optimum condition was 0,023 U/ml. Macroalgae from Tanjung Tiram water was a potential source of amylase enzyme for food or pharmaceutical industry purposes